Peran Manajemen Bimbingan dan Konseling (BK) dalam Menanggulangi Kenakalan dan Kesulitan Belajar Siswa di SMK Sultan Agung 1 Tebuireng Jombang - Iva Inayatul Ilahiyah (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2017)
Guidance and counseling is very important in educational institutions because through guidance and counseling program can help smooth and facilitate school program and help students find their jatidirinya through some guidance and counseling program that can solve problems faced by students, giving advice for students who have difficulty in learning and also develop student's talents and interests. Efforts taken by guidance and counseling teachers are service and implementation of guidance and counseling and cooperate with all organizations. To this end, this study focuses on: (1) How is the management of guidance and counseling in SMK Sultan Agung 1 Tebuireng Jombang?, (2) How is the role of guidance and counseling management in overcoming student learning difficulties in SMK Sultan Agung 1 Tebuireng Jombang?, and (3) How is the role of guidance and counseling management in developing the talents and interests of students in SMK Sultan Agung 1 Tebuireng Jombang?. The research was conducted by using qualitative approach with case study design. The data collection technique in this research is using three approaches, namely: (1) Observation, (2) interview, and (3) method of documentation. The data analysis techniques performed are: data collection, data reduction, data presentation, temporary conclusion, verification and final drawing. Data validity criteria are based on extension of participation, persistence, and triangulation. This study yielded several findings; First, the concept of guidance and counseling in SMK Sultan Agung 1 Tebuireng Jombang are: a) Guidance and counseling at SMK Sultan Agung 1 Tebuireng Jombang includes 12 guidance and counseling services are: orientation service, placement and distribution service, individual counseling services, group counseling services , learning services, information services, group guidance services, guidance and counseling instruments, case conflicts, hand over cases, data collection and home visit; b) The steps of guidance and counseling in SMK Sultan Agung 1 Tebuireng Jombang include Step Analysis, Step Synthesis, Step Diagnosis, Step Prognosis, Follow-up and Provision of assistance; c) The benefits of guidance and counseling in SMK Sultan Agung Tebuireng Jombang is to help develop the talents and interests of students, help solve student problems, provide guidance for students who have difficulty in learning. Second, management guidance and counseling in SMK Sultan Agung 1 Tebuireng has been developed and implemented through several programs that are through planning, organizing, implementation or actuating and evaluation or controlling with the aim of providing assistance to students to know their identity and solve problems experienced by students and develop student talents and interests. Third, guidance and counseling efforts in tackling delinquency and learning difficulties students in SMK Sultan Agung 1 Tebuireng Jombang is through: Corrective and Peservatif. Fourth: The effort of guidance and counseling in developing talents and interests of students in SMK Sultan Agung 1 Tebuireng Jombang is through: Understanding, Preventive, Corrective and Peservatif